Group f.64 : Edward Weston, Ansel Adams, Imogen Cunningham, and the community of artists who revolutionized American photography /: Edward Weston, Ansel Adams, Imogen Cunningham, and the community of artists who revolutionized American photography. (2014) - Unknown
No abstract available